The Relationship Social Support With The Adherence To Taking ARV Medication - nirwanto k rahim; Yuniar M Soeli (Universitas Negeri Gorontalo, 2023)
Human immunodeficiency virus or better known as HIV, is a virus that infects the human immune system. Several factors, including social support, influence compliance with PLWHA undergoing ARV treatment. Social support is verbal or non-verbal information, advice, real help, or behavior provided by people familiar with the subject in their social environment. This study aims to determine the relationship between social support and adherence to ARV treatment at peer support shelters in Gorontalo City. This study used a correlational design. The sample used was 37 respondents using the Total Sampling method. Data was collected using a questionnaire sheet and analyzed with univariate and bivariate. Based on the study's results, good social support in this study amounted to 29 respondents or 78%, while social support was not as good as 8 respondents or 21%. So, a significant relationship exists between social support and adherence to ARV medication. Suggestions from this study Nurses can implement the findings of this study in providing nursing care, especially in preventive efforts to drop out of ARV drugs